Kendali Kecepatan Motor BLDC dengan metode Mesin Sinkron dan Variasi PWM berbasis IoT - Asep Andang; Rahayu, Andri Ulus; Imam Taufiqurrahman; Ervan Paryono (P3M Politeknik Negeri Cilacap, 2025)
This study investigates speed control of brushless DC (BLDC) motors using a synchronous machine method and Pulse Width Modulation (PWM) variations based on IoT. A three-phase inverter controlled by an STM32 microcontroller was used to drive the BLDC motor. Speed control was implemented by adjusting the inverter frequency based on the synchronous machine principle, while PWM duty cycle was varied to regulate the input voltage. An IoT-based system using a smartphone app allowed remote speed settings. Experimental results showed that the synchronous machine method could effectively control BLDC motor speed, with frequency changes linearly affecting inverter output voltage. Varying PWM duty cycles impacted the voltage required to achieve target speeds, with higher duty cycles requiring lower voltages. The control system achieved speed accuracies within 3% of setpoints across different duty cycles. This approach demonstrates the feasibility of applying synchronous machine principles for BLDC motor control with IoT integration.